Improvement of geotechnical properties of local clay by using fly ash - Muhammad Wazizi Hamzar, Abdul Aziz. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Soft soil improvement and stabilization has been widely practised for a long time by mixing admixtures such as lime , cement and pond ash to increase the strength of the soil. Different types of admixtures were also used as stabilizers to improve the stiffness and strength of a clay soil. As for this study, the objective is to analyze the improvement in local clay soil when being stabilized by using fly ash from the local coal plant. Tests were first made to study the characteristics of the clay soil. Then s amples are prepared carefully to prevent inconsistencies between them since the outcome of each tests must be related to each other in o rder to produce a significant results. Standard Proctor Test and Unconfined Compression Strength (UCS) Test are the main tests used in this study. From the analyzed data, there is a significant increase in strength when the clay sample were mixed with fly ash and the trend continues until the addition of 20 percent fly ash to the sample. The sample containing 20 percent fly ash tends to sustain more loads during the compression tests. The strength of each samples increased until the seventh day of curing, before gradually decreasing. However, the strength of the samples regained after the fourteenth day. As a conclusion , local clay can also be stabilized or improved by using fly ash, and this may become as a starting step for future assessments that could lead to more soil improvement for ground soil in Malaysia.